2009
DOI: 10.1055/s-0029-1216363
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Normal Perisellar Anatomy in 1.5 T T2-weighted MRI and Comparison with the Anatomic Criteria defining Cavernous Sinus Invasion of Pituitary Adenomas

Abstract: Inter- and intra-individual variations of the perisellar anatomy and its relation to the pituitary gland exist, which are partly related to age and AH. This must be remembered when the invasiveness of pituitary adenomas is assessed in MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Sasagawa et al 5 , were the only relating grade of resection with ICD. In their study gross total or subtotal resection was less achieved in patients with ICD lower than 25 mm, however, the aforementioned distance is still higher than the mean ICD found in ours and other studies, so we do not recommend that measurement as an obstacle to tumor resection 1,3,4,5,6,22,23,25,27,28,29 . In conclusion, apparently the ICD at the horizontal segment of the cavernous carotid tends to be wider in patients with giant pituitary adenomas.…”
Section: A B C Dcontrasting
confidence: 78%
See 1 more Smart Citation
“…Sasagawa et al 5 , were the only relating grade of resection with ICD. In their study gross total or subtotal resection was less achieved in patients with ICD lower than 25 mm, however, the aforementioned distance is still higher than the mean ICD found in ours and other studies, so we do not recommend that measurement as an obstacle to tumor resection 1,3,4,5,6,22,23,25,27,28,29 . In conclusion, apparently the ICD at the horizontal segment of the cavernous carotid tends to be wider in patients with giant pituitary adenomas.…”
Section: A B C Dcontrasting
confidence: 78%
“…The mean values for the intercarotid distance at the selar region in healthy individuals reported in the literature have a wide range, varying from 12 mm to 18 mm 1,3,4,6,22,23,25,27,28,29 , what we believe to be related to the method used to measure the distance and the ethnical differences between the study populations. In our study, the mean intercarotid distance at its horizontal portion at the sellar region (ICD2) in the controls group was 19.41 ± 3.00 mm, a difference probably attributable to the same reasons they differ in another studies.…”
Section: Discussionmentioning
confidence: 79%
“…For this reason the MWCS appears as a hypointense line running between the hyperintense CS and tumor/normal tissue in coronal images. In the present study, PDWI detected all MWCSs, whereas T2-weighted images were reported to detect only 33% of the MWCSs [19]. To increase the signal-to-noise ratio and reduce scanning time, our image resolution was sacrificed by reducing it from 512 × 512 pixels to 403 × 448 pixels, which was still acceptable and corresponded to a change in image pixels from 0.35 mm to 0.40 mm.…”
Section: Discussionmentioning
confidence: 56%